Effect of Resource Factors and Quality of Instruction on Performance in Mathematics of Nigeria Secondary School Students - Abdullahi, Umar; Sirajo, Musa (Universitas Sembilanbelas November Kolaka, 2020)
It seems that Nigeria's educational system has been undergoing improvement only on quantitative when it comes to the number of enrolments in students and schools. However, little effort has been put in place in terms of capacity (physical and material resources, human and financial resources) to manage high enrollment. Resources capacity in secondary schools was nothing to write home about. Most of these resources in secondary school were dilapidated. To worsen the scenario, the scarce resources allocated to these schools are grossly inadequate compared to students' enrollment and come late to the end-users in the public secondary schools. The various stakeholders in the education sector express stern concern about the consistently poor performance of students in secondary schools, especially in mathematics. Since secondary school education is expected to be free by the government, coupled with population increase, it is reasonable for people to take advantage of the free education program. Although the government and private sector of education keep providing qualified teaching staff and non-teaching staff, students in secondary schools still face poor performance in mathematics. The effect of all these on the academic performance in Nigeria's mathematics secondary school students concerns researchers of this empirical work. It is based on these issues and many more that this work sought to empirically investigate the impact of resource factors and quality of instruction on the performance of Nigeria secondary school students in mathematics.